Historical blocking: MM 2021-04-26 to 2021-04-28 (Myanmar) - Voidly (2021)
CRITICAL severity censorship detected in Myanmar. Confidence: 80%. Data sourced from ooni-historical-backfill.
Censorship Incident ID: MM-2021-0036
Keywords: censorship; MM; censorship; critical